Reformulation of the Prosecutor’s Office’s Regulatory Role in the Legislative Process for Sustainable Economic Development - I Gede Willy Pramana; Gde Made Swardhana; Desak Putu Dewi Kasih; Sagung Putri M.E. Purwani (Pelopor Publikasi Akademika, 2026)
The phenomenon of sustainable economic development in Indonesia reveals the increasing complexity of national strategic policies and projects, which necessitate preventive and sustainable legal safeguarding. Normatively, the Indonesian Prosecutor's Office is positioned not only as a repressive law enforcement body but also as an institution with preventive and protective functions through its law enforcement intelligence authority, as stipulated in Article 30B of Law Number 11 of 2021 concerning Amendments to Law Number 16 of 2004 concerning the Prosecutor's Office of the Republic of Indonesia (the Amendment to the Prosecutor's Law). However, its implementation reveals that the Prosecutor's Office's role in the legislative process and development policy planning has not been optimally actualized. Juridically, this is due to the ambiguous norm (vague norm) in Article 34 of the Amended Prosecutor's Law, which uses the permissive phrase